THE EFFECT OF LEADERSHIP, QUALITY OF HUMAN RESOURCES AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT UTSMAN BIN AFFAN LIBRARY, INDONESIAN MUSLIM UNIVERSITY MAKASSAR - Fhara, Fhara; Najib, Muh; Hasan, Hamzah (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
The purpose of this study was to determine the influence of leadership, quality of human resources and organizational culture on employee performance at the Utsman Bin Affan Library of UMI Makassar. The population of this research is the total number of employees within the Utsman Bin Affan library at UMI Makassar, totaling 30 people. The research approach used is descriptive quantitative. Data collection was carried out by distributing questionnaires and literature study. Processing and data analysis using the latest version of the SPSS application. The results of this study indicate that based on partial testing, leadership variables, human resource quality, and organizational culture have a positive and significant effect on employee performance at the Utsman Bin Affan UMI Makassar Library. This can be seen from the value of t-count> t-table, namely 2.98 which is obtained from df2 = 26; α = 0.05 and it can also be seen from the significance level value <0.05, namely the leadership variable with the t-test 3.121> 2.98 or the significance 0.004 <0.05 (significant effect), the variable quality of human resources with t-test 3.566> 2.98 or a significance of 0.001 <0.05 (significant effect), and the organizational culture variable with t-count 3.006> 2.98 or a significance of 0.002 <0.05 (significant effect).